PERANCANGAN SISTEM INVENTORY STOK BARANG PERUSAHAAN CV INDIKA PRAYUDATAMA - Achmad hersa prayudhatama, (2021)
With various kinds of businesses in their fields of wanting to build the company's management, sales and purchase data will play a very important role in company management, it really must be considered in the progress of a company, one of which is by increasing the recap of data within the company, with the aim of designing a stock inventory system. This is an attempt to find out the turnover of goods in the company. This proposed system design uses the waterfall method. This application utilizes technology to support the company's vision, namely professionals in data processing. In the application of the inventory, an application design will be made, it aims to process data that will be processed into a document. By using HTML and CSS on website pages along with the PHP programming language and the XAMPP server using MYSQL. It is hoped that this system can be useful in processing sales and purchasing data so that good management results in effective achievement.